The impact of cadre deployment on the audit and financial performance of provincial departments : the case of selected provincial departments in Limpopo Province, South Africa - Ramatlhale, Kgantshi Jones (My University, 2024)
This study examined the impact of the cadre deployment policy on the audit and financial performance of the selected provincial departments in Limpopo, South Africa. The AGSA report 2021/22 indicated that several departments, such as health, in Limpopo, still face compliance challenges. The report indicates negligence in the legislation that carries out public mandates set out by their institutions. There is also a need for consequence management. The 2019/20 report by the late and former AG Kimi Makwetu stated that the Limpopo Health Department is among these departments, which needs to be fixed or more functional regarding financial performance. Underpinning this dysfunctionality was mismanagement due to political instability or interference, corruption, and incompetence, often resulting in poor service delivery, thus prolonging the periods of underdevelopment and inadequate access to essential services. This study argues that cadre deployment partly contributes to the dysfunctionality of public sector institutions. This has been noted in various departments in Limpopo, such as the Department of Health and Treasury, where cadre deployment has infiltrated such institutions' departments and operations. These institutions are mandated to deliver services to the people; thus, the effect has been riots, adverse audit outcomes, protests, and irregular expenditure, especially at the provincial government level. This results in participatory exclusion regarding collective development, which must be characterised by public participation. To answer the guiding questions of this study, a qualitative research approach was adopted where semi-structured interview guides were distributed to three selected departments in Limpopo. Findings revealed that the quest for effective governance, consistent financial performance, and clean audit outcomes in South Africa’s public sector depends on the availability of competent staff with the required skills. It was revealed that cadre deployment promotes a culture of impunity and lack of accountability. The policy undermines the functioning of the public, thus contributing to a breakdown of governance and service delivery. As such, this will have widespread implications for inclusive development, poverty eradication, and good governance free from corruption and nepotism.
Thesis (MPA.) -- University of Limpopo, 2024
Keywords: Cadre Deployment; Corruption; Audit Outcome; Financial Performance; Implications; Provincial Government; Political corruption -- South Africa; Finance, Public -- Auditing; Compliance auditing; South Africa -- Politics and government